2021
DOI: 10.3390/app11146652
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment of Different Waste Lubrication Oil Management Options in Serbia

Abstract: On average, approximately 22 thousand tons of new lubrication oil were marketed annually in Serbia in the period 2015–2019. Less than 20% of the waste lubrication oil (WLO) generated was treated, whereas the remainder was mostly uncollected or improperly disposed of. The purpose of this study is to examine different WLO management scenarios that could be implemented in Serbia in the future and to quantify their potential environmental benefits. Different WLO treatment processes (namely the re-refining of used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…As the main problem in Serbia, it is stated that a very low share of waste is recycled -e.g. PET bottles (11%) (Schmidt et al 2020) or lubrication oil (less than 20%) (Dudjak et al 2021).…”
Section: Waste Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…As the main problem in Serbia, it is stated that a very low share of waste is recycled -e.g. PET bottles (11%) (Schmidt et al 2020) or lubrication oil (less than 20%) (Dudjak et al 2021).…”
Section: Waste Managementmentioning
confidence: 99%
“…They concluded that the state of the circular economy in Serbia is in an unenviable position. The circular economy in Serbia has not been implemented in practice yet, but experts from several fields are dealing with this topic (Ilić &Nikolić, 2016;Stevanovic-Crapina et al 2016;Milanović et al 2020;Denčić-Mihajlov et al 2020;Demirović Bajrami et al 2020;Schmit et al 2020;Dudjak et al 2021;Rakascan et al 2021;Kosanović et al 2021;Bucea-Manea-Țoniş et al 2021).…”
Section: The State Of Circular Economy In Serbiamentioning
confidence: 99%
“…It includes all the phases of the entire existence of a product, from its manufacture to the end-of-life recovery phase, with its negative impacts (resources, emissions, discharges, and unusable waste) and positive impacts (new jobs, reuse of components, new resources). This significant capacity to consider the environmental impact of a product as a whole makes this methodology one of the most widely used in the environmental scientific literature [31][32][33][34][35][36][37]. It is used to analyse the environmental impact all the way from renewable energies [38][39][40][41] to the construction industry [42,43] or food products [44].…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…For the sustainability of resources and improve environmental, economic, and social advantages, a strategic approach to waste lubricant oil management through utilization activities is crucial (Botas et al, 2017) (Du đak et al, 2021. The Ministry of Environment and Forestry must grant permits for any use of hazardous waste (Pemerintah Republik Indonesia, 2021).…”
Section: Introductionmentioning
confidence: 99%